Designing the profile of industrial consumers of renewable energy in Romania under the impact of the overlapping crisis - Grosu, Veronica; Socoliuc, Marian; Ciubotariu, Marius Sorin; Hlaciuc, Elena; Tulvinschi, Mihaela; Macovei, Anamaria Geanina; Melega, Anatol (Frontiers in Energy Research, 2022)
Prior to the outbreak of the conflict in Ukraine, the European energy markets had already been in a profound state of crisis with prices reaching top levels and with minimum supplies. The cost of the energy has had a significant impact on the performance and the sustainability of the majority of the economic operators, most of them considering the overgrowth of the price of the energy and the raw materials as the main risks in terms of the short - term development of the operational activity. Given the current situation, the aim of the study is to identify new solutions to reduce the negative effects of the present day crisis on the Romanian economic operators. In this context, the study focuses on the following objectives: O1—estimating the social and economic effects on the economic operators as a result of the energy crisis; O2—identifying the key factors which make the economic operators switch from the traditonal resources consumption to the renewable energy consumption and O3 - analyzing the influence factors in stimulating the investments in the renewable energy. The research methods that have been used are based on the quantitative analysis with the help of a questionnaire applied to 264 Romanian production companies. The final results of the present study refer to designing an overall profile of the industrial consumers given the escalation of the energy crisis worldwide. The findings of the study can be useful both for the final energy consumers and for the producers and distributors alike and ultimately for the European and national legislators whose decisions are closely related to the very future of these economic entities.